Long-term treatment outcome in chronic myeloid leukemia patients in accelerated phase treated with imatinib (glevec®) - L. A. Antipova; S. S. Loria; S. V. Semochkin; A. G. Rumiantsev (Онкогематология)
The purpose of this study was evalueted of a long-term treatment outcome in chronic myeloid leukemia (CML) patients in accelerated phase treated with GlivecR and determination of an optimum therapy schedule. 105 patients (men — 46, women — 59) at the age from 15 till 74 years (a median age — 40 years) enrolled between 02.2001 and 02.2007 were studied. Treatment started a dose of 600 mg/day. At the insufficient primary therapy response or loss complete hematological and/or complete cytogenetic remission in the course of treatment, dose have been increased to 800 mg/day. In 82 (78.1%) patients complete hematological remissions have been reached. In 44 (41.9%) patients complete cytogenetic response (CR) is received, and in 27 (61.4 %) of them with molecular response: complete — 17 (63%) and major — 10 (27%). 6-year overall survival rate (OS) was 61.9%, 6-year event-free survival rate (EFS) — 30.5%. Achievement of complete CR was a predictor of long longterm survival rate: OS — 95.5% versus 37.7 % (р <0.001). In case of absence CR (n=16) imatinib dose escalation allowed to receive complete CR in 5 (31.25%) and minor — in 4 (25.0%) patients. Loss or absence of complete CR on imatinib therapy not always leads to CML progression: in 18 (17.1 %) patients without complete CR hematological parameters remain normal and there are no signs of disease progression.